The functions of law - Ehrenberg, Kenneth M. (Oxford : Oxford University Press, 2016)
What is the nature of law and what is the best way to discover it? This book argues that law is best understood in terms of the social functions it performs wherever it is found in human society. To support this claim law is explained as a kind of institution and as a kind of artefact, providing a novel understanding of law's nature.
This edition previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on May 4, 2016).
Keywords: Law -- Philosophy; Law; Jurisprudence & general issues